Genome-wide association analysis provides molecular insights into natural variation in watermelon seed size. Issue 1 (19th January 2022) - Gong, Chengsheng; Zhao, Shengjie; Yang, Dongdong; Lu, Xuqiang; Anees, Muhammad; He, Nan; Zhu, Hongju; Zhao, Yong; Liu, Wenge
Abstract: Watermelons used for seed consumption tend to have larger seeds, whereas watermelons used for flesh consumption often require relatively small seeds. Therefore, watermelon seed size has received extensive attention from consumers and breeders. However, the natural variation and genetic mechanism of watermelon seed size remain unclear. In the present study, 100-seed weight, seed hilum length, seed length, seed width, and seed thickness were examined in 197 watermelon accessions. Furthermore, association analysis was performed between seed size traits and high-quality SNP data. The results revealed that there were strong correlations among the five seed traits, and seed enlargement was an important feature during watermelon seed size domestication. The seed-consumed biological species Citrullus mucosospermus and the edible seed watermelon Citrullus lanatus had significantly larger seeds than the other species. Eleven non-repeating significant SNPs above the threshold line were obtained from GWAS analysis. Four SNPs on chromosome 5 were considered to be closely associated with seed size traits (S5:32250307, S5:32250454, S5:32256177, and S5:32260870) and could be used as potential molecular markers for the breeding of watermelon cultivars with a target seed size. In addition, based on gene annotation information and previous reports, five genes near the four significant SNPs may regulate seed size. qRT-PCR analysis showed that two genes that may be involved in abscisic acid metabolism, Cla97C05G104360 and Cla97C05G104380, may play an important role in regulating watermelon seed size. Our findings provide molecular insights into natural variation in watermelon seed size and valuable information for molecular marker-assisted breeding.